Peningkatan Pengetahuan Parenting Ibu-Ibu Melalui Kegiatan Penyuluhan Dalam Pencegahan Stunting Dusun Jengglong Desa Tegalweru - Ramadani, Rizki Tri; Roziqin, Khairur; Sutanti, Widya Dhana Juniar; Fikri, Shofil; Munawara, Munawara; Jauhar Rahmatullah, Muhammad Reza Dhia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Poor parenting has a risk of being stunted 8 times greater than research subjects with good parenting Stunting is a lack of nutrition in children that disrupts child growth. According to the 2019 Social and Nutrition Survey of Indonesian Toddlers (SSGBI) reported that the prevalence rate of stunted children in Indonesia was 27.3%, this stunting prevalence rate has decreased in 2022. This study aims to increase parenting knowledge in preventing stunting. This study used a quasi-experimental type of research with the pretest-postest method. This study tested this research design to determine the level of knowledge of respondents before being given the intervention and after being given the intervention and to find out more accurate results related to the effective success of parenting counseling in preventing stunting. The results of this study were an increase in knowledge of the correct percentage before counseling of 72% and increased after counseling to 89%.